The Implementation of IoT to monitor water quality in snakehead (Channa striata) bio floc in Desa Marta jaya, Kabupaten Ogan Komering Ulu: Penerapan IoT dalam menjaga kualitas air Kolam Bioflok Budidaya Ikan Gabus Di Desa Marta Jaya, Kabupaten Ogan Komering Ulu - Tompunu*, Alan Novi; Rarassari, Madyasta Anggana; Inayatullah, Ahlam; Claudya Nurcahaya; Muharramah, Ulfah; Seprianto, Dicky; Zamheri, Ahmad; Zakaria, Zakaria (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Pokdakan Karya Mandiri Jaya is a group of fish farmers located in Marta Jaya Village, Ogan Komering Ulu Regency, South Sumatra Province. The main problem faced by Pokdakan Karya Mandiri Jaya is the relatively low survival rate of snakehead fish. This group is only able to produce 5000 snakehead fish larvae at a time spawning with the survival rate of the snakehead fish becoming adult snakehead fish around 70-75%. This is due to a decrease in water quality caused by the accumulation of leftover feed which is not handled regularly. Therefore, a system is needed to monitor pH, temperature and turbidity of water so that cultivators can take initial preventive measures. Service activities are carried out in three stages, the first stage was analytical situation, the second is planning and the last is implementation. The IoT device that was previously installed has already carried out the calibration process. The calibration results showed that the IoT tool can be used in the Pokdakan Karya Mandiri Jaya snakehead fish cultivation. It is hoped that from the application of IoT technology, Pokdakan Karya Mandiri Jaya can reduce the risk of death of snakehead fish and increase snakehead fish production.